2013
DOI: 10.1111/cpr.12023
|View full text |Cite
|
Sign up to set email alerts
|

Fractone‐heparan sulphates mediate FGF‐2 stimulation of cell proliferation in the adult subventricular zone

Abstract: Our results demonstrate that FGF-2 requires HS to stimulate cell proliferation in the SVZa and suggest that HS associated with fractones and vascular basement membranes are responsible for activating FGF-2. Therefore, fractones and vascular basement membranes may function as a HS niche to drive cell proliferation in the adult neurogenic zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 69 publications
0
42
1
2
Order By: Relevance
“…niche (Douet et al, , 2013Kerever et al, 2007;Mercier and 68 Arikawa-Hirasawa, 2012; Mercier and Douet, 2014a,b). Although 69 our previous studies demonstrate a critical role of fractones in 70 adult neurogenesis, the effect of aging on fractones structure and 71 composition remains to be elucidated.…”
mentioning
confidence: 99%
“…niche (Douet et al, , 2013Kerever et al, 2007;Mercier and 68 Arikawa-Hirasawa, 2012; Mercier and Douet, 2014a,b). Although 69 our previous studies demonstrate a critical role of fractones in 70 adult neurogenesis, the effect of aging on fractones structure and 71 composition remains to be elucidated.…”
mentioning
confidence: 99%
“…Earlier studies characterizing the three matrices found that spinal cord ECM contained relatively lower levels of sulfated glycosaminoglycans, 20 and it has been shown that glycosaminoglycans such as heparan sulfate, chondroitin sulfate, and hyaluronan influence NSC proliferation. [51][52][53] Differences in NSC and perivascular stem cell mitogenic and chemotactic responses to the ECMs might also differ based on their unique protein profiles (Fig. 1) and biomolecular constituents, including laminin, myelin, and collagen, all of which vary between the ECMs.…”
mentioning
confidence: 99%
“…Intriguingly, endothelial fractones were also shown to contact BrdU + NSCs thus allowing, in principle, a direct signaling by CSF factors to NSCs (Kerever et al, 2007). It was indeed shown that FGF2 contained in CSF is efficiently captured by heparan sulfate on fractones and stimulates SVZ cell proliferation (Douet et al, 2013). Similarly, CSFderived BMP4 efficiently attached to SVZ fractones, but in this case had an inhibitory effect on NSC proliferation (Mercier and Douet, 2014).…”
Section: The Svz Vascular Nichementioning
confidence: 99%